O apóstolo da anarquia: quatro décadas de militância de José Oiticica - Fernandes, Andre Santoro [UNIFESP] (2020)
This research aims to analyze the militancy of the anarchist José Rodrigues Leite and Oiticica between 1910s and 1940s. In addition to being a respected professor and intellectual, he dedicated most of his life to political practice, participating in various events related to the working class (in general) and anarchists (in particular). As a militant, tried to direct his actions towards different segments, also highlighting his anti-clericalism. In this process, Oiticica dedicated himself to social advertising in a broad way, publishing papers in different journals and giving interviews on topics related to the reality of workers. Based on his life trajectory and his vast textual production, this study analyzes some aspects of his political performance: his goals as a militant; the anarchism he demanded; his proposals for an anarchic communist-based social organization. In addition, he tried to examine his time’s problems, elaborating critics of the social surveillance organization using his own analytical instrument. The sources that support this research are diversified, including periodicals from both the militant press and the mainstream press; police records; correspondences and the booklet “The Anarchist Doctrine within the reach of all”. Written by Oiticica, this work synthesizes part of his conceptions and policies, including, for example, his Theory of State.